Generational differences, socialisation effects and 'mobility links' in international holiday travel. (January 2022) - Mattioli, Giulio; Scheiner, Joachim; Holz-Rau, Christian
Abstract: International holiday travel was rapidly growing until the COVID19 crisis and was widely expected to continue on such a trajectory for decades. This is consistent with long-term trends towards the expansion of activity spaces and the increasing importance of high-speed modes of travel. This would suggest that young adults today had earlier and more frequent experience of cross-border holiday travel than previous generations, with possible knock-on effects in terms of socialisation to increased international mobility. Previous research has also suggested the existence of self-reinforcing dynamics in international mobility over individual life courses and across family generations. The concept of "mobility links" points to such effects, whereby e.g., international mobility experience leads to more foreign trips later in the life course and/or in the subsequent generation. Robust quantitative evidence of such trends and associations, however, has remained elusive due to the lack of adequate data. We use unique data from Dortmund (Germany) including detailed retrospective information on holiday travel and life course events for a large sample of students, their parents, and grandparents. Our results show: i) a rapidly increasing trend in international holiday travel behaviour (trip frequency and age at first trip) across three generations; ii) from a socialisation perspective, associations between international holiday frequency and age at first holiday abroad among students; iii) from an intergenerational perspective, associations between the holiday practices of students and their parents. We conclude by discussing implications for further research on mobility biographies and the 'institutionalisation' of international travel, as well as policy implications.